Experiências vivenciadas por alunos com deficiência visual em instituições de ensino superior na cidade de Uberlândia - MG - Ferreira, Lavine Rocha Cardoso (2010)
Currently, there are significant advances in research and production of material with views of including the visually impaired in educational places, as well as various other sectors of society. However, people with visual disabilities face many difficulties in their schooling process such as: the lack of professionals with specific training needed to work with this specific population, the absence of thorough knowledge on behalf of society about the visually impaired, the myths still surrounding these disabilities, and the difficulty to access different social places, including education. This study investigates the experiences of students with visual impairment in higher education institutions in the city of Uberlândia-MG. The aim of this study is to describe the schooling of the subjects studied, identify key facilities and difficulties faced by them in the daily life of institutions, and analyze the pedagogical aspects of the academic context. In this descriptive-exploratory, qualitative approach, data collection was organized from semi-structured audio-recorded interviews. The study was carried out between November 2008 and May 2009, with thirteen subjects, nine with little vision and four blind, enrolled in courses of Music, History, Physics, Mathematics, Language, Social Service, Education, Communications and Therapy, from four institutions, one public and three private. The analysis of experiences, based on studies on the subject showed that technological resources are facilitators of learning and encourage those without vision to pursue college degrees, even though in the investigated institutions, resources are not yet sufficiently appropriate to the needs of disabled visual. The study confirms data of other studies regarding the preparation of the professor, indicating the need for specialized teachers for assistance in academic activities and for the effective inclusion of persons with visual impairments.